Curious minds eaudiobook A knight and moon novel. - Evanovich, Janet (Knight and Moon, 2016)
NEW YORK TIMES BESTSELLER • Janet Evanovich, bestselling author of the Stephanie Plum series, teams up with Emmy-winning writer Phoef Sutton for a brand-new series of mysteries featuring Emerson Knight and Riley Moon, a dynamic duo with instant and undeniable chemistry.   Emerson Knight is introverted, eccentric, and has little to no sense of social etiquette. Good thing he’s also brilliant, rich, and (some people might say) handsome, or he’d probably be homeless. Riley Moon has just graduated from Harvard Business and Harvard Law. Her aggressive Texas spitfire attitude has helped her land her dream job as a junior analyst with mega-bank Blane-Grunwald. At least Riley Moon thought it was her dream job, until she is given her first assignment: babysitting Emerson Knight.   What starts off as an inquiry about missing bank funds in the Knight account leads to inquiries about a missing man, missing gold, and a life-and-death race across the country. Through the streets of Washington, D.C., and down into the underground vault of the Federal Reserve in New York City, an evil plan is exposed. A plan so sinister that only a megalomaniac could think it up, and only the unlikely duo of the irrepressibly charming Emerson Knight and the tenacious Riley Moon can stop it. Praise for Curious Minds   “The one-liners fly at a ferocious pace. . . . Evanovich fans will find this closer in style to the Stephanie Plum novels.” — Booklist   “Evanovich’s comedic timing and pacing are evident on every page.” —Daily Republic